To the issue of solving the inverse tasks of multi-criteria identification of volume hydraulic machines - Stryczek, Jaroslaw; Lurye, Zinoviy Yakovlevich; Solovyov, Volodimir Mikhaylovich; Antoniak, Piotr (NTU "KhPI", 2017)
The work proves the effectiveness of the parameter space investigation method for solving inverse tasks of multi-criteria identification by the example of an external gear pump with a transparent casing developed at the Wroclaw Polytechnica. The mathematical model of the object of investigation was improved by introducing the equations of radial clearance and normal backlash, which increased its adequacy and allowed to determine three input data that are absent in the technical documentation. The found values of the dedendum coefficient, backlash and radial clearance together with other known input data allow to build the 3D computer model for further investigation of pump working processes in the CFD program.

У роботі обґрунтовано ефективність методу дослідження простору параметрів для рішення зворотних задач багатокритеріальної ідентифікації на прикладі шестерінчастого насоса зовнішнього зачеплення з прозорим корпусом, розробленого у «Вроцлавській політехніці». Покращена математична модель об'єкта дослідження шляхом введення рівнянь радіального і нормального бокового зазорів, що підвищило її адекватність і дозволило визначити три вихідних даних, відсутніх у технічній документації. Знайдені значення коефіцієнта висоти ніжки зуба, бічного і радіального зазорів спільно з іншими відомими вихідними даними дозволяють побудувати 3D комп'ютерну модель для подальшого дослідження в програмі обчислювальної гідродинаміки робочого процесу насоса.
До питання рішення зворотних задач багатокритеріальної ідентифікації об'ємних гідромашин
Keywords: mathematical model; inverse identification tasks; direct identification tasks; multi-criteria identification tasks; adequacy criteria; ідентифікація; математична модель; критерії адекватності